Pengaruh Dukungan Keluarga, Urgensi Komunikasi Dan Literasi Teknologi Terhadap Efektifitas Dan Preferensi Work From Home (Studi pada Pegawai Dinas Kesehatan Kabupaten Tegal) - Inayah Inayah; Siti Puryandani (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study aims to analyze the effect of family support, communication urgency, technological literacy on the effectiveness of WFH and WFH preferences in the Tegal District Health Office. The population in this study were all Tegal District Health Office employees who worked during the COVID-19 pandemic. The data used is primary data from distributing questionnaires to employees as respondents with a sample of 91 respondents. Data analysis using SEM PLS. The sampling technique used is to use a saturated sample design or a census, which is a sampling technique that thoroughly provides equal opportunities or opportunities for all elements or members of the population to be selected as samples. The results showed that family support, communication urgency, technological literacy had a significant positive effect on the effectiveness of WFH and the effectiveness of WFH was not proven to have a significant effect on WFH preferences.